Independent factors of flow velocity indices in common carotid artery - Noor Azmi, Azran Azhim; Sakagami, K.; Ueno, Akinori; Kinouchi, Yohsuke; Fukuyama, Ryo (Springer Berlin Heidelberg, 2013)
Several parameters were used to investigate differences in aging rates influenced by cardiovascular risk factor. We sought to identify independent predictors modulating velocity indices in common carotid artery (CCA) from large population of normotensive and hypertensive to predict health risk. We studied a total of 254 subjects between 20 and 70 years of age who were classified into three groups: Group III (control), Group II (pre-hypertensive) and Group 3 (hypertensive) as depended on their blood pressure levels. Weight, body mass index, visceral fat and waist circumference in hypertensive subjects were significantly higher than control subjects. Because of the peak systolic and peak diastolic velocities decreased in hypertensive subjects, therefore their resistive index (RI) decreased and their velocity reflection index (VRI) increased. After adjusting for age and exercise status, women had higher diastolic velocity components and second systolic velocity. Women had a significant greater VRI (P <0.0001), smaller RI (P=0.001) and lower vascular elastic recoil (VEI) (P=0.005) than in men. The VRI which was superior to RI and VEI had higher dependence on age, gender, diastolic blood pressure, heart rate, and weight (adjusted R 2=0.736). In conclusion, velocity reflection index can be used as an important predictor of hypertensive and obesity risk.